2022
DOI: 10.1038/s41598-022-21412-z
|View full text |Cite
|
Sign up to set email alerts
|

The dominant mesopredator and savanna formations shape the distribution of the rare northern tiger cat (Leopardus tigrinus) in the Amazon

Abstract: Understanding the distribution patterns of threatened species is central to conservation. The Amazonian distribution of the northern tiger cat (N-tiger cat, Leopardus tigrinus) and its interspecific relationship with the ocelot, its potential intraguild killer, are intriguing. Here, we combined presence/absence records with species distribution models (SDMs) to determine N-tiger cat occurrence in the Amazon. We also modeled ocelot density from 46 published estimates. The N-tiger cat’s presence in the Amazon wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
(42 reference statements)
2
12
0
1
Order By: Relevance
“…As previously shown by de Oliveira et al 42 , and confirmed again here, savanna tiger-cats are absent from the rainforest formations of Amazonia (except for the Tocantins forest ecoregion), and are restricted mostly to its savanna enclaves. The difference in the range in Amazonia between our model and that of de Oliveira et al 42 relates to the different approaches used (MAXENT vs. GLM models).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As previously shown by de Oliveira et al 42 , and confirmed again here, savanna tiger-cats are absent from the rainforest formations of Amazonia (except for the Tocantins forest ecoregion), and are restricted mostly to its savanna enclaves. The difference in the range in Amazonia between our model and that of de Oliveira et al 42 relates to the different approaches used (MAXENT vs. GLM models).…”
Section: Discussionsupporting
confidence: 91%
“…As previously shown by de Oliveira et al 42 , and confirmed again here, savanna tiger-cats are absent from the rainforest formations of Amazonia (except for the Tocantins forest ecoregion), and are restricted mostly to its savanna enclaves. The difference in the range in Amazonia between our model and that of de Oliveira et al 42 relates to the different approaches used (MAXENT vs. GLM models). Additionally, in our land cover variable we excluded open savanna formations, resulting in large areas of the Rupununi and Sipaliwini savannas unsuitable for savanna tiger-cats, whereas in de Oliveira et al 9 , both areas in their entirety were classified as suitable.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interspecific interactions are one of the key factors that shape species behavior and occurrence [1][2][3][4]. Species occurrence and distribution are also shaped by environmental constraints.…”
Section: Introductionmentioning
confidence: 99%